PENELITIAN SUSU DAN HOMOGENISASI MEDIA BESAR MENGGUNAKAN MEDIA LACTIC M37 DAN PENGARUHNYA PADA NILAI GIZI KEJU - Hamzah, Basuni (Jurnal Dinamika Penelitian Industri, 2010)
Skim milk homogenization at 7 (single stage), 71 and 176 kg/cm2(dual stage,35 kg/cm2 second stage )Was used in the manufacture of cottage cheese. Each lots of skim milk manufactured into cottage cheese was inoculated with lactic culture M37.Bulk stater of lactic culture M30 was homogenized at 0,35(single stage ),106,and 246 kg/cm2 (dual stage 35kg/cm2 second stage).the use of 4 deifferent bulk culture with 3 different skim milk treatment produced a total of 12bulk starter skim milk treatment combinations. All 12 bulk starter skim milk treatment combinations were randomized prior to their manufacture. The experiment was relicated four time to manufacture of 48 vats of cottage cheese. Either homogenization of skim milk at 71 kg/cm2(dual stage, 35kg/cm2second storage)or greater or homoginezation of bulk culture at 246kg/cm2(dual stage, 35kg/cm2second storage) reduced yield loss